Factors affecting IgG4-mediated complement activation - Oskam, Nienke; Damelang, Timon; Streutker, Marij; Ooijevaar-de Heer, Pleuni; Nouta, Jan; Koeleman, Carolien; Van Coillie, Julie; Wuhrer, Manfred; Vidarsson, Gestur; Rispens, Theo (Frontiers in Immunology, 2023)
Of the four human immunoglobulin G (IgG) subclasses, IgG4 is considered the least inflammatory, in part because it poorly activates the complement system. Regardless, in IgG4 related disease (IgG4-RD) and in autoimmune disorders with high levels of IgG4 autoantibodies, the presence of these antibodies has been linked to consumption and deposition of complement components. This apparent paradox suggests that conditions may exist, potentially reminiscent of in vivo deposits, that allow for complement activation by IgG4. Furthermore, it is currently unclear how variable glycosylation and Fab arm exchange may influence the ability of IgG4 to activate complement. Here, we used well-defined, glyco-engineered monoclonal preparations of IgG4 and determined their ability to activate complement in a controlled system. We show that IgG4 can activate complement only at high antigen and antibody concentrations, via the classical pathway. Moreover, elevated or reduced Fc galactosylation enhanced or diminished complement activation, respectively, with no apparent contribution from the lectin pathway. Fab glycans slightly reduced complement activation. Lastly, we show that bispecific, monovalent IgG4 resulting from Fab arm exchange is a less potent activator of complement than monospecific IgG4. Taken together, these results imply that involvement of IgG4-mediated complement activation in pathology is possible but unlikely.